2010
DOI: 10.5735/085.047.0505
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Chemical and Physical Treatments on Seed Germination ofErica australis

Abstract: We studied the germination of Erica australis seeds and their responses to different treatments (high temperature, acidic condition, cold stratification, gibberellic acid applications). Germination was very low in untreated seeds (3%) and required approximately one month to start, but increased in all the treatments tested, reaching a value of 100% when seeds were treated with gibberellic acid (25 ppm). Exposure to heat and to low pH promotes germination and reduces time to germinate, which indicates that germ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
8
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 29 publications
2
8
0
Order By: Relevance
“…No increased germination in simulated-winter or simulated-spring in LS soils in comparison with ES was observed, as would have been expected if cold requirements or other mechanisms of physiological dormancy had been present (Baskin and Baskin 1998). These data corroborate laboratory experiments that showed that cold exposure is not required for germination in several groups of Mediterranean species (Giménez-Benavides et al 2005;Luna et al 2008), although this may not apply to all shrubby species (Trigueros Vera et al 2010). As discussed above, the impact of these changes in the relative temporal patterns of germination on the shrub-herbs interactions is probably not very important since the simulated-autumn germination peak was dominant, although field studies need to verify this.…”
Section: Discussionsupporting
confidence: 88%
“…No increased germination in simulated-winter or simulated-spring in LS soils in comparison with ES was observed, as would have been expected if cold requirements or other mechanisms of physiological dormancy had been present (Baskin and Baskin 1998). These data corroborate laboratory experiments that showed that cold exposure is not required for germination in several groups of Mediterranean species (Giménez-Benavides et al 2005;Luna et al 2008), although this may not apply to all shrubby species (Trigueros Vera et al 2010). As discussed above, the impact of these changes in the relative temporal patterns of germination on the shrub-herbs interactions is probably not very important since the simulated-autumn germination peak was dominant, although field studies need to verify this.…”
Section: Discussionsupporting
confidence: 88%
“…Germination after fire in the field is delayed in time with respect to the other two species; autumn rainfall triggering germination in Cistus and Rosmarinus was not as efficient for doing so in Erica, whose germination was delayed until later in the winter or spring (Quintana et al, 2004). Cold stratification is also required for germination in Erica australis, a species common in these shrublands (Trigueros Vera et al, 2010). Furthermore, germination after fire in this species can be delayed by several months (Valbuena et al, 2000).…”
Section: Emergence Recruitment and Fire Seasonmentioning
confidence: 98%
“…Colonization and survival data were collected at 5 months. For the seedling experiment, seeds were stored in the freezer for 3 months to aid stratification and break dormancy (Vera, Martin & Oliva 2010). Prior to sowing, seeds were surface-sterilized for 30 s in 1Á5% calcium hypochlorite, rinsed with distilled water and then sown directly in 50-mL tubes (three per tube) filled with the peat:sand mixture.…”
Section: N O C U L a T I O N E X P E R I M E N T Smentioning
confidence: 99%